2022
DOI: 10.3390/agronomy12122977
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antagonist Potential of Selected Compost Bacterial Isolates (CBI) against Plant and Human Pathogens

Abstract: Several fecal and enteric pathogens are present within the primary organic raw materials that are introduced to compost piles. These pathogens may compete with the existing microbiota and limit their efficiency, yielding only partial decomposition of the final compost. These pathogens also affect the process kinetics and persist in the final compost or may even regrow as a result of the declining effect of indigenous antagonistic micro-organisms. In this work, 11 indigenous bacterial isolates were selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In most cases, these microbiota are not active in the decomposing process, and/or have low antagonistic potential regarding their secondary metabolites. Thus, they are subjected to severe competition by existing pathogens such as Listeria monocytogenes and Salmonella Typhimurium [36]. For this, the selection and application of an abundant number of adapted microorganisms, especially Actinobacteria and fungus, existing naturally in the environment, which can be easily invested and used in the pretreatment of biomass, targeting cellulose and hemicelluloses [37], helps to fasten the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, these microbiota are not active in the decomposing process, and/or have low antagonistic potential regarding their secondary metabolites. Thus, they are subjected to severe competition by existing pathogens such as Listeria monocytogenes and Salmonella Typhimurium [36]. For this, the selection and application of an abundant number of adapted microorganisms, especially Actinobacteria and fungus, existing naturally in the environment, which can be easily invested and used in the pretreatment of biomass, targeting cellulose and hemicelluloses [37], helps to fasten the process.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [36], eleven bacterial isolates, including three different strains of Bacillus subtilis (CBI 1, CBI 2, and CBI 7), two different strains of Providencia sp. (CBI 3 and CBI 11), Alcaligens sp.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the number of microbes, the higher is the rate of decomposition. The secondary metabolites produced by the microbes in the inoculum suppresses the growth of other microbes and in turn results in composts with high nutritive value [8]. It is suggested that, humification of lignin waste which is present in excess will increase the concentrations of ligninase, protease, xylanase and urease.…”
mentioning
confidence: 99%
“…Solid waste management has become a major issue in several developing countries in recent times [8]. Nutrient retrieval from organic wastes such as kitchen litter, agro-waste, and municipal waste is crucial for waste management and environmental fortification.…”
mentioning
confidence: 99%